RABIES ORAL IMMUNIZATION AGAINST RABIES - Hussain, Khalid A. (The Iraqi Journal of Veterinary Medicine, 1998)
Rabies is a highly fatal infection of the central nervous system which occur in all warm-blooded animals and transmitted by the bites of affected animals. The major manifestations of the disease include motor irritation and clinical signs of mania and an attack complex and ascending paralysis. Rabies and rabies related viruses belong to a group of more than 75 viruses called RHABDOVIRUSES (Rhabdo=rod) because of their bullet-shaped morphology. The virus is fragile, easily inactivated by disinfectants, and does not exist free in the environment. Instead, in the course of its infection in reservoir host species, it is shed into the saliva and is transmitted by bite. After entry into a new host in the bite site, rabies virus multiplies in muscle cells and aggregates around the proprio receptor nerve endings of their acetylcholine receptors and then spreads through neural pathways, all without stimulating an effective host immune response. Transmission depends on simultaneous delivery of virus to the salivary glands and the limbic system of the brain. Infection of the limbic system of the brain is the cause of the fury which drives the animal to bite. Infection of the salivary glands is the source of the large amounts of virus in saliva. This unique pathogenetic patterns leads to entrenchment of the virus in its reservoir host populations and to continuing risk of exposure of man. Dog rabies has been controlled globally by the use of potent vaccines and the application of effective urban control programs (poisoning trapping shooting). The problem that then remained has been wildlife rabies, primarily in wolves, foxes, skunks, raccoons as well as stray dogs. Therefore, a new approach to wildlife rabies control has been made which involves oral vaccination. Several successful trials were attempted in Switzerland, West Germany and the U.S.S.R. Rabies control efforts in the developing countries did little to really reduce the incidence of the disease. Therefore, mass vaccination of dogs and the elimination of strays coupled with the oral vaccination (recombinant vaccinia vaccine) of dogs so that the population of susceptible stray dogs can be immunized.